BUDAYA DAMAI DI PESANTREN: STUDI TERHADAP AL-ISLAM GUMUK - Siti Muawanah (Harmoni, 2013)
Pondok Pesantren is an islamic boarding school that has recently obtained big attention because it is associated with radicalism and terrorism; even to some people the institution is regarded as fertile ground to sow the seeds of such violence. Although some other people strongly argue that the accusation is totally wrong, the negative stigma could not disappear easily. Using qualitative approach, this writing describes the peace culture in al- Islam Gumuk, a pesantren in Solo which most people are “fear” of. The results show that despite potential to conflict, this pondok pesantren still sow the culture of peace, such as tolerance, equality, justice, freedom, and individual rights.